Faktor Yang Mempengaruhi Keberhasilan Pemberian Asi Eksklusif di Desa Nauli Kec. Sigumpar Kab.Toba - Munarni Simatupang (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Efforts to increase the provision of breast milk (ASI) play a very big role in achieving infant mortality rates and reducing the prevalence of malnutrition in children under five. This research aims to determine the factors that influence the success of exclusive breastfeeding. This research design is descriptive analytical with a sample size of 26 respondents using a total sampling method. The results of this research were that the majority of respondents aged 26-30 years were 10 people (38.5%), the majority of respondents had secondary education as many as 19 people (73.1%), the majority of respondents were housewives as many as 20 people (76.9%), the majority of respondents had income < 1,000,000 as many as 22 people (84.6%), and the majority of children are one child as many as 17 (65.4%). Data analysis using product moment. From the results of the product moment statistical test, it can be concluded that management factors in the birthing place that support breastfeeding and providing breastfeeding facilities in public places are factors that influence the success of exclusive breastfeeding. The relationship between management at the birth center that supports breastfeeding and exclusive breastfeeding obtained a value of r = 0.458, which means the relationship between the two variables has a sufficient relationship, and obtained a value of P = 0.019, meaning there is a significant influence. And for the relationship between providing breastfeeding facilities in public places and exclusive breastfeeding, the value obtained was r = 0.394, which means that the two variables have a sufficient relationship, and the value obtained was P = 0.047, which means there is a significant influence.